Assesment of variability and individual responses to resistance training: an integrative statistical framework - Manzano Pedrós, Sergi (2025)
Systematic resistance training (RT) is a well-established method to induce neuromuscular adaptations. However, studies consistently report heterogeneous responses among individuals, including potential “non-responders” or negative responders to standardized training protocols. This variability has driven interest in assessing individual-level responses to personalize RT interventions. Notedly, evidence for individual response is commonly inferred from variability in intervention effects, but true differences in trainability (i.e., caused by the training intervention) must isolate subject-by-training interaction variance from random error and within-subject variability. Quantification of variability also aids with categorizing individual training responses. Dichotomic methods classify individuals as either “responders” or “non-responders” based on a response threshold of relevance. Alternative methods consider the continuous range of likelihood of response by adding confidence intervals (CI) to each response estimate. The study of individual responses demands specific methodological and analytical considerations, but rigorous application of these in RT studies is currently limited. The purpose of this study was to integrate several methods for the assessment of variability and individual responses in skeletal muscle strength and size to a RT intervention.